The orthostatic hypotension in patients with Stanford type A aortic dissection after surgery. (11th May 2022) - Funaki, T; Kanazawa, M; Takahashi, S; Seki, T; Iguchi, A; Kagaya, Y; Sato, K; Saito, H; Kondo, M; Miura, M; Kawatsu, S; Endo, H; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Orthostatic hypotension (OH) is sometimes observed during cardiac rehabilitation in patients with surgery for aortic dissection. However, little is known about the primary determinant of OH and influence of surgical range on incidence of OH. Purpose: The aim of this study was to elucidate the incidence of OH in patients with surgery for aortic dissection, and compare it between the patients with ascending aortic replacement surgery (ascending group) and those with ascending aorta and hemiarch or total arch replacement surgery (arch group). Methods: We analyzed 59 patients who underwent emergent surgery due to Stanford type A aortic dissection from January 2014 to March 2018, and compared the incidence of OH between ascending group (n = 28, age 69.8 ± 11.3 years) and arch group (n = 31, age 64.1 ± 13.0 years). Results: The incidence of OH in total patients was 30.5%. There were no significant differences in patient characteristics including body tall, body weight, antihypertensive use and progress of rehabilitation between 2 groups. The arch group showed a significant higher incidence of OH as compared with ascending group (arch group: 46.4% vs. ascending group: 16.1%, p = 0.03). Moreover, the patients who occurred OH were significantly taller than those who did not occur OH. Conclusions: OH was observed in about one third of patients with surgery for aortic dissection and it showed a close relationship with patient's height and the range repaired by surgical operation. More careful cardiac rehabilitation is needed for tall patients with large area replacement of aorta.